PERAN ORGANISASI PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) TERHADAP PROGRAM PEMBERDAYAAN PEREMPUAN DI KELURAHAN SUKOREJO KECAMATAN GUNUNGPATI SEMARANG - Kusumaningsih, Sabtarini; Rianawati, Titik (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
Women’s Empowerment is one of the programs created by the Family Welfare Empowerment Organization (PKK) especially in the city of Semarang, with the aim of exploring and developing the potential of women in order to help them have the insight and ability to improve the welfare of their families. The method used in this research is a qualitative description method using qualitative information or data which is described descriptively with the aim of exploring a phenomenon or social reality. The variables in this research are the role of Family Welfare Empowerment Organizations (PKK) and Women’s Empowerment Program. While the results of this reseach are the role of Family Welfare Empowerment Organizations (PKK) in helping women especially in the Sukorejo sub-district, Gunungpati sub-district, Semarang city, in exploring and developing their potential.